INLA GOES TO SCHOOL AUGMENTED REALITY ANALYSIS AND DESIGN - Yonky Pernando; Axel Arya Maitri Cundana (STMIK Royal, 2021)
Abstract: lThis study describes the INLA Goes to School Gymnastics activities which have temporarily not been running for a year due to the pandemic. Therefore, this study makes analysis and design which will later be made into applications for further research so that INLA goes to school Gymnastics activities can be carried out again during a pandemic and after a pandemic. lAugmented Reality is a technology that allows users to see a combination of real and virtual objects in a real environment and run in real time or realtime. lIn this study, the author makes a 3-dimensional animation design to make it look more attractive and increase interest in using the INLA Goes to School Augmented Reality Gymnastics application. The INLA Goes to School Gymnastics Application Based on Augmented Reality was created using the Unity application and in the animation stage using the Blender application. Keywords: analysis; Android; application; augmented reality; INLA Abstrak: 1Penelitian ini mendeskripsikan tentang kegiatan Senam INLA Goes to School yang sementara belum berjalan selama setahun dikarenakan oleh pandemi. Maka dari itu penelitian ini membuat Analisa dan desain yang nantinya akan dibuatkan aplikasi dipenelitian selanjutnya agar kegiatan Senam INLA goes to school dapat dilakukan kembali disaat pandemic dan sesudah pandemi. Augmented Reality merupakan teknologi yang memungkinkan pengguna melihat gabungan benda nyata dan maya di lingkungan yang nyata dan berjalan pada waktu yang nyata atau realtime. 1lDalam penelitian ini, dapat membuat desain animasi 3 dimensi agar tampilan lebih menarik dan menambah minat dalam penggunaan aplikasi Augmented Reality Senam INLA Goes to School. 1Aplikasi Senam INLA Goes to School Berbasis Augmented Reality ini dibuat dengan menggunakan aplikasi Unity dan dalam tahap animasi menggunakan aplikasi Blender. Kata kunci: analisis; android; aplikasi; augmented reality; INLA